2009
DOI: 10.2976/1.3111282
|View full text |Cite
|
Sign up to set email alerts
|

The Tumbleweed: Towards a synthetic protein motor

Abstract: Biomolecular motors have inspired the design and construction of artificial nanoscale motors and machines based on nucleic acids, small molecules, and inorganic nanostructures. However, the high degree of sophistication and efficiency of biomolecular motors, as well as their specific biological function, derives from the complexity afforded by protein building blocks. Here, we discuss a novel bottom-up approach to understanding biological motors by considering the construction of synthetic protein motors. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 82 publications
1
59
0
Order By: Relevance
“…The model could be extended to include reverse chemical rate transitions to study the physical mechanism of the recently observed processive backward stepping of myosin V under superstall load forces (26). This type of model could also be used to model the dynamics of molecular motors at filament intersections (27,28), to study the more complex cooperative gating of multiple motors attached to a single cargo (29), or in the design of synthetic molecular motors (30).…”
mentioning
confidence: 99%
“…The model could be extended to include reverse chemical rate transitions to study the physical mechanism of the recently observed processive backward stepping of myosin V under superstall load forces (26). This type of model could also be used to model the dynamics of molecular motors at filament intersections (27,28), to study the more complex cooperative gating of multiple motors attached to a single cargo (29), or in the design of synthetic molecular motors (30).…”
mentioning
confidence: 99%
“…A completely rigid motor will have less diffusional space to explore and may bind more quickly than a completely flexible motor. But, previous modeling results have shown that a rigid motor is very sensitive to the binding site separation (determined by the structure of the dsDNA track), and thus it is also not clear a priori which optimal flexibility minimizes the diffusional search time [11].…”
Section: Introductionmentioning
confidence: 98%
“…Designing an artificial molecular motor using protein components may thus provide insight into subtle structurefunction aspects of biomolecular motors. We have proposed an artificial motor concept, the Tumbleweed (TW), which uses proteins as motor building blocks [11]. Proteins offer more diverse design choices than oligonucleotide structures because of the relatively large set of available amino acid building blocks that can produce large, three-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations